BANDUNG MUSIC ARENA, GEDEBAGE BANDUNG - Heksania, Sulfa
Bandung as the capital of West Java has a high potential in the field of performing arts and music. Various musical performances are often held each year, ranging from traditional ones such as angklung choirs, gamelan, until the modern concert from indie bands, mainstream bands, and solo artist. However, the development of the public interest towards music is not accompanied by any supporting facilities that adequate enough. Therefore this city required a location or area that can serve as the public attractors. The location is then expected to become a center and generator of music development in Bandung. Provision of the music hall in the primary center Gedebage deemed necessary by the government to address these needs. Bandung Music Arena is a music hall typology building for regional scale performing arts in the city of Bandung. The building is designed to meet the needs of musical performances in the city of Bandung in the form of a concert hall’s city representative which is currently not available in Bandung, as well as part of the center that represents the color of Indonesian music and the young generation itself.